Decellularization of Pig Lung to Yield Three-Dimensional Scaffold for Lung Tissue Engineering - Čimborová, Katarína; Kotasová, Hana; Pelková, Vendula; Sedláková, Veronika; Hampl, Aleš (Methods in molecular biology, 2024)
Lately, the need for three-dimensional (3D) cell culture has been recognized in order to closely mimic the organization of native tissues. Thus, 3D scaffolds started to be employed to facilitate the 3D cell organization and enable the artificial tissue formation for the emerging tissue engineering applications. 3D scaffolds can be prepared by various techniques, each with certain advantages and disadvantages. Decellularization is an easy method based on removal of cells from native tissue sample, yielding extracellular matrix (ECM) scaffold with preserved architecture and bioactivity. This chapter provides a detailed protocol for decellularization of pig lung and also some basic assays for evaluation of its effectivity, such as determination of DNA content and histological verification of the selected ECM components. Such decellularized scaffold can subsequently be used for various tissue engineering applications, for example, for recellularization with cells of interest, for natural ECM hydrogel preparation, or as a bioink for 3D bioprinting.
Keywords: extracelulární matrix; Animals; plíce; Extracellular Matrix; tkáňové podpůrné struktury; Tissue Engineering; tkáňové inženýrství; zvířata; Hydrogels; Lung; prasata; Swine; Tissue Scaffolds; hydrogely